Nuclear Star Clusters in Coma confirmation of an unusually high nucleation fraction. Issue Volume 15:Issue S359(2020) (March 2019) - Zanatta, Emilio; Sanchez-Janssen, Ruben; Chies-Santos, Ana L.
Abstract: Nuclear star clusters (NSCs) are stellar systems similar in size to globular clusters (GCs) but extremely dense, comparable only to some GCs and ultra-compact dwarfs. They are present in galaxies with a wide range of masses, morphologies and gas content. There are several formation scenarios proposed for the formation of such objects, such as the merger of GCs or extreme star formation caused by the inflow of gas. Recent studies show that the presence of an NSC is related to galaxy stellar mass. Moreover, it has been suggested that NSCs are more often found in high density environments. In our work, we use deep imaging of the core regions of the Coma cluster down to an absolute magnitude of –8.2 and found that in this environment the nucleation fraction is higher than in the Virgo and Fornax clusters. We find nucleated galaxies in Coma as faint as –11.2 mag.